KETERAMPILAN BELAJAR MAHASISWA - Suprayekti Suprayekti (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2010)
The purpose of this study is to describe the learning skills of the students at the Curriculum and Educational Technology Department. The study is classified as a descriptive inquiry applying survey technique. The data were collected using a set of questioner with five alternative choices: Always, Often, Sometimes, seldom, and never. Fifty out of 397 student were chosen as samples using incidental sampling technique. The data were analyze quantitavely using simple statistics technique. The result of the study indicates, the learning skills of the students categorized good with the average score of 74,29% covering routine learning activities and preparation for examination.